How to foster informed decision making about food supplements: results from an international Delphi study. Issue 4 (1st June 2019) - de Vries, Hein; Pajor, Emlia M; Curfs, Kenny C J; Eggers, Sander M; Oenema, Anke
Abstract: Food supplement use can have beneficial and detrimental effects, making informed decisions about supplement use important. How these decisions are made and which communication strategies can stimulate informed decision making is unclear. This study identified the important characteristics of (i) informed decision making about food supplement use and (ii) important factors indicating how to communicate about food supplements to foster informed decision making. An online three-round Delphi study was conducted. International experts within the field of (risk) communication about food supplements or related fields were recruited via email. The participants' age ranged from 25 to 69 years, and sample sizes for the three rounds were 38, 89 and 51, respectively. Experts indicated that for making an informed decision about food supplement use one needs to have knowledge of their positive and negative effects, the ability to compare these effects, knowing alternatives besides supplements, feeling informed, and feeling able (self-efficacious) to make the decision and making the decision voluntarily. Important communication strategies mentioned were: provision of information about positive and negative effects and the nature of these effects including scientific evidence, ensuring information is easily accessible, well ordered, tailored and provided by a trustworthy, credible and independent source.